Cycling to school: building the case for sustainable micromobility practices in Portugal - Fialho, S. (2024)
Transports account for a very large share of the total amount of greenhouse gas emissions in a vast number of countries and currently, this sector is responsible for the highest volume of carbon dioxide emissions in Portugal. In a country with a significant car dependency, it is worth studying what prevents and encourages sustainable micromobility practices, in particular the simple act of cycling to school. Borrowing perspectives from Social Practice Theory, this paper analyses several examples ofsuccess stories recently experienced across Europe and North America - “bike bus”, “bicibús”, “cycling bus”, “comboio de bicicletas” - as well as the benefits that were outlined by participating communities. It then focuses on parents who have their children attending three different Portuguese schools located in the municipality of Seixal. The survey results are highlighting the elements that can contribute to a higher adoption of such practices, through the lenses of Social Practice Theory. This paper offers a set of guidelines that could contribute to promoting similar initiatives in Portugal, in particular in urban areas such as the Metropolitan Area of Lisbon.